Large hepatocellular carcinomas: treatment with transarterial chemoembolization alone or in combination with percutaneous cryoablation. (31st December 2018) - Cui, Wei; Fan, Wenzhe; Huang, Kunbo; Wang, Yu; Lu, Mingjian; Yao, Wang; Li, Jiaping
Abstract: Purpose: To evaluate the safety and efficacy of transarterial chemoembolization (TACE) combined with cryoablation (TACE-cryoablation) in large (main tumor ≥5 cm in diameter) hepatocellular carcinomas (HCCs). Methods: From January 2010 to December 2015, 56 patients were treated with combination therapy via a single TACE session followed by one to three percutaneous cryoablation sessions twice a week (TACE-cryoablation group). A total of 54 patients were treated with TACE alone for two to six sessions once a month (TACE group). The decision between TACE and TACE cryoablation was based on patient choice. Outcomes of patients in two groups were compared according to the largest tumor diameter (subgroup): Group A (5 cm ≤ tumor <10 cm), Group B (10 cm ≤ tumor <15 cm), and Group C (tumor ≥15 cm). Results: The mean number of cryoablation sessions per patient was 2.3 (range: 1–6). Within Group B, TACE-cryoablation significantly improved survival compared with TACE alone (11.0 vs 6.0 months; p  = .008). This was also seen in Group C (8.0 vs 5.0 months; p  = .001). However, no significant difference was noted in Group A (17.0 vs 13.0 months; p  = .674). The complications related to TACE were comparable between the two groups. Two adverse events of grade 3 − 4 related to cryoablation occurred in two patients (3.6%). The independent prognostic factors for survival included: TACE cryoablation, AFP level, main tumor size and extrahepatic metastasis. Conclusions: TACE-cryoablation may improve overall survival in patients with HCC who presented with a tumor diameter ≥10 cm, with minimal complications, when compared with TACE alone.